Revisiting high-density lipoprotein cholesterol in cardiovascular disease: Is too much of a good thing always a good thing? - Mohammad Al Zein (20090700) (2024)
Cardiovascular disease (CVD) continues to be a leading cause of global mortality and morbidity. Various established risk factors are linked to CVD, and modifying these risk factors is fundamental in CVD management. Clinical studies underscore the association between dyslipidemia and CVD, and therapeutic interventions that target low-density lipoprotein cholesterol elicit clear benefits. Despite the correlation between low high-density lipoprotein cholesterol (HDLC) and heightened CVD risk, HDL-raising therapies have yet to showcase significant clinical benefits. Furthermore, evidence from epidemiological and genetic studies reveals that not only low HDL-C levels, but also very high levels of HDL-C are linked to increased risk of CVD. In this review, we focus on HDL metabolism and delve into the relationship between HDL and CVD, exploring HDL functions and the observed alterations in its roles in disease. Altogether, the results discussed herein support the conventional wisdom that “too much of a good thing is not always a good thing”. Thus, our recommendation is that a careful reconsideration of the impact of high HDL-C levels is warranted, and shall be revisited in future research. Other Information Published in: Progress in Cardiovascular Diseases License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.pcad.2024.10.009